Da escola sem sentido à escola sem função: por uma constituição da Skholé - Petry, Clériston (2017)
In the present thesis, I present an investigation about the specificity of the school in the context of the “new capitalism” and its ramification “neoliberal”, extracting a scholar typology empashized by the “learning language” instead of the “educational language”. In a context that everything becomes “productive time”, the problem resides in thinking a school that would found itself in a different logic from the interests of family, of society, of politics, and, specially, of the “new capitalism”. I proceed, then, with an interpretation of a collection of bibliographies seeking to establish a conceptual mark about the fundamental characteristics of this context, evidencing the instrumental and utilitarian character of the school that, consequently, loses its specificity and weakens the essence of education, which is the “natality” (Arendt). It is about pushing the concepts and making them explicit with arguments, aiming to redefine them, defending, thus, a meaning of the school beyond the “new capitalism”. I defend, therefore, that the “new capitalism” has crystallized elements of Modernity such as the disconsideration of the past, the pathos of the new, and, in some manner, the conversion of all the spheres and experiences in “labor/work”. This has converted the school in to a space of “production” and/or “consuming”, evidenced by the introduction of a business management lexicon in the school language. A school able to preserve the newness of “new generations”, that gives to them the opportunity of experiencing themselves and experiencing the world as “new”, can only be a institution that is conservative of the “free time” established in the “present time” (skholé). In the “new capitalism”, the school may become the only space that people have the opportunity of experiencing the world and themselves without the injunctions of the utility or the functionality. In the school, the world is deprivatized, turned public, a thing, an here and a now. This occurs experiencing the world, manipulating it and acting; answering the questions of the “subjects”, of the colleagues and of the teachers; thinking about what has happened and what happens; inserting children and young people in to the world, in its languages, culture and past, supported by the safety, care and responsibility of the adults. If in the “new capitalism” the individuals feel that they can’t control time anymore, because there is not a long term, the school is the counterpoint of that, a moment and an event that does not have the concern about killing time, spending the time or being under the control of the clock. The skholé is the privileged time and space for studying, thinking and acting. Without this updated conception of skholé, the school cannot be scholastic. In somber times, the skholé is the hope that we deposit in the arrival of each new generation.